Prove that √3/(sin /9) − 1/(cos /9)=4
Answers
Answered by
0
Answer:
LHS =
(cos9
∘
−sin9
∘
)
(cos9
∘
+sin9
∘
)
Divide by Nr and Dr by cos9
∘
LHS =
1−tan9
∘
1+tan9
∘
=
1−tan45
∘
tan9
∘
tan45
∘
+tan9
∘
where tan45
∘
=1
=tan(45+9) using compound angles formula
=tan54
∘
=tan(90−36)=cot36
∘
Hence Proved
Answered by
0
Step-by-step explanation:
refer to the attachment for answer.
Attachments:
![](https://hi-static.z-dn.net/files/d16/9311bd900597d6d43e4626efddf62dce.jpg)
Similar questions
Hindi,
1 month ago
Math,
1 month ago
English,
1 month ago
Math,
2 months ago
Math,
2 months ago
Political Science,
10 months ago
Computer Science,
10 months ago
Computer Science,
10 months ago